CO2 hydrogenation to methanol and dimethyl ether by Pd–Pd2Ga catalysts supported over Ga2O3 polymorphs - Oyola Rivera, Oscar (2015)
The production of methanol and dimethyl ether (DME) via CO2 hydrogenation was studied using Pd catalysts supported on a-Ga2O3, a-b-Ga2O3 and b-Ga2O3 polymorphs. The formation of a Pd2Ga intermetallic compound was observed using XRD and XPS. The catalytic activity improves with an increase in the content of the Pd2Ga intermetallic compound. The content of Pd2Ga on Pd/Ga2O3 depends on the Ga2O3 crystalline phase of the catalyst. A slight catalytic deactivation was observed for all samples studied. The Pd/a-b-Ga2O3 catalyst displayed the largest deactivation. The deactivation appears to be caused by a loss of basic sites. The selectivity to dimethyl ether is not dependent on the Pd2Ga content, but depends on the catalyst acidity. This assertion was tested by adding niobia to the catalysts, thus increasing the DME selectivity from 0 to 53%. The content of Pd2Ga over Pd/Ga2O3 catalysts was identified to be a crucial parameter for CO2 hydrogenation to methanol.